The Educational First Field Supervisors’ Practice Of The Transformational Leadership Supervision Skills: Teachers’ Prespectives In The Sultanate Of Oman - Khulood Ahmed Amur Alobaidani; Noorhayati Hashim; Mohammad Najib Jaffar (Usuli Faqih Research Centre PLT, 2024)
This quantitative study is to investigate the degree of the educational supervisors’ practice of the first field to the educational supervision transformational leadership skills, from the teachers’ perspective. The problem is that the educational supervisor does not practice transformational leadership. The objectives included: the extent of the first field educational supervisors’ practice of the transformational leadership behavior, which includes four areas: ideal effect, mental arousal, inspirational motivation and individual considerations. The researcher adopted the analytical descriptive method, a random sample of (65) first field teachers was selected. A questionnaire of (16) paragraphs was used to measure the extent of the educational supervisors’ practice of transformational leadership, by (4) paragraphs to measure each area. For data analysis, the statistical package (SPSS) and the Pearson correlation coefficient were used to measure the interconnections of the scales and axes of the scale, and the Cronbach alpha coefficients. The findings showed that the degree of practice of the educational supervisor of supervisory leadership was (medium) with an average of (3.33) and a standard deviation of (1.311). The results of the sample responses varied between the large and middle grades. The mean ranged between (3.46) and (2.92).